2016
DOI: 10.1007/s11684-016-0476-5
|View full text |Cite
|
Sign up to set email alerts
|

Mouth the mirror of lungs: where does the connection lie?

Abstract: Periodontitis is the chronic destructive disease of the periodontium (Gums) caused by host bacterial interactions. The effect of such host bacterial interactions in oral cavity also evokes a systemic response. Numerous studies have found common mechanisms of destruction for periodontal diseases and other chronic diseases like diabetes mellitus, atherosclerosis, respiratory diseases, and adverse pregnancy outcomes. Oral colonization by respiratory pathogens appears to be a risk factor for development of respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 34 publications
0
17
0
3
Order By: Relevance
“…A study indicated that daily personal oral hygiene measures decrease the risk of respiratory diseases. 64 Meanwhile,…”
Section: Discussionmentioning
confidence: 99%
“…A study indicated that daily personal oral hygiene measures decrease the risk of respiratory diseases. 64 Meanwhile,…”
Section: Discussionmentioning
confidence: 99%
“…Obligate anaerobes are one of the common causative bacteria of pneumonia, especially aspiration pneumonia. Anaerobic lung infection can occur after aspiration of salivary secretions, especially in patients with periodontal disease, and the increase in gram‐negative anaerobes in the oral cavity induced by poor oral hygiene is thought to be responsible for causation of pneumonia …”
Section: Introductionmentioning
confidence: 99%
“…1,2 In this context, also oral health might play a key role, as a recent review article points the association between oral health, especially periodontal inflammation, and respiratory diseases. 3 Beside of that special condition, patients after organ transplantation in general should be early dental rehabilitated and the demand of a sufficient maintenance is present in literature. [4][5][6] In contrast, recent investigations on the oral health situation of transplant recipients show insufficient dental and periodontal health, as well as shortcomings in dental behavior of patients after solid organ transplantation, including lung, liver, and kidney.…”
Section: Introductionmentioning
confidence: 99%